THE SUITABILITY OF ACTIVITIES IN THE TRADE SUB-ZONE (THE CORRIDOR OF LETDA SUJONO ROAD, MEDAN TEMBUNG SUB-DISTRICT, MEDAN CITY) - Trisilia Pohan; Feby Milanie; Cut Nuraini; Abdi Sugiarto (International Journal on Livable Space, 2024)
The development of population and infrastructure in cities can enhance the local economy, as seen in the Letda Sujono Road corridor. This area, located between Medan City and Deli Serdang Regency and near the Bandar Selamat Toll Gate, has seen significant growth in trade and service activities. This growth has spurred the development of housing, public services, commercial spaces, warehousing, and industry, increased land demand and causing potential land-use conflicts and traffic issues. Inappropriate space utilization can lead to urban sprawl, often due to inadequate spatial planning control. The Medan City Detailed Spatial Plan (DSP or Rencana Detail Tata Ruang (RDTR)) designates the Letda Sujono Road corridor as a Trade Sub-zone, with zoning regulations limiting some activities to 10% of the block area. Aims: The objective of this study was to study the suitability of existing activities with the zoning plan which has been regulated in the Medan City Detailed Spatial Plan as a space control content in order to create safe, comfortable and sustainable spatial planning. Methodology and results: This study uses a qualitative descriptive method with spatial analysis to assess the alignment of current activities with the DSP zoning plan. Conclusion, significance and impact study: The findings reveal that 60.84% of the activities are suitable, while 39.16% are not. Some blocks, particularly Block 17-07-01 (Tembung), have exceeded the 10% activity limit, indicating that zoning plans have not been fully realized, with unauthorized activities such as integrated schools and vehicle-related services still present.